'Goose bumps'-associated anaemia. (22nd August 2011) - Hoshino, Chisho; Yamabe, Akane; Sekikawa, Yoshiyuki; Ishihara, Kana; Ikeda, Hiroshi; Satoh, Noriyuki; Narita, Masashi; Inoue, Minoru
Abstract : A 36-year-old woman presented to our hospital for further evaluation of anaemia screened by regular check-up. She was diagnosed with iron-deficiency anaemia (IDA) but refractory to iron supplementation. She had negative results of occult blood in the stool and no gynaecologic disease potentially causing hyper menorrhea. Upper endoscopy revealed a nodular gastritis, which has been called 'Torihada-ien', a Japanese word meaning 'gastritis with goose bumps-like appearance', associated with Helicobacter pylori (Hp) infection. After Hp eradication therapy, her anaemia resolved with an improved response to iron supplementation. In an unexplained IDA patient, Hp-associated gastritis should be considered in the possible background.